2017
DOI: 10.1084/jem.20160903
|View full text |Cite
|
Sign up to set email alerts
|

AKR1B1 promotes basal-like breast cancer progression by a positive feedback loop that activates the EMT program

Abstract: The treatment of BLBC represents an unmet medical need. Wu et al. show that AKR1B1 facilitates BLBC progression through a positive feedback loop that activates the EMT program, suggesting that inhibition of AKR1B1 has the potential to become a valuable therapeutic strategy for BLBC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
94
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(108 citation statements)
references
References 62 publications
7
94
0
Order By: Relevance
“…In cancer, AKR1B1 has been found to have a role in the growth and the aggressiveness of cancer cells (27), but was never associated with cancer cells' EMT, CSCs, or related pathways, until recently. Wu and colleagues, in fact, reported that AKR1B1 can induce EMT via PGF2a synthesis and NFkB activation in triple-negative breast cancer cells (42). On the basis of the data here presented, which point at the PP as strongly connected to EMT as well as the plasticity of other types of cancer cells, it is possible to speculate that the same enzyme has multiple ways to regulate EMT (in a tissue-specific manner).…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…In cancer, AKR1B1 has been found to have a role in the growth and the aggressiveness of cancer cells (27), but was never associated with cancer cells' EMT, CSCs, or related pathways, until recently. Wu and colleagues, in fact, reported that AKR1B1 can induce EMT via PGF2a synthesis and NFkB activation in triple-negative breast cancer cells (42). On the basis of the data here presented, which point at the PP as strongly connected to EMT as well as the plasticity of other types of cancer cells, it is possible to speculate that the same enzyme has multiple ways to regulate EMT (in a tissue-specific manner).…”
Section: Discussionsupporting
confidence: 54%
“…Furthermore, the observed tissuespecific changes in the AKR1B1/SORD coexpression pattern ( Supplementary Fig. S5) suggest the importance of investigating the transcriptional regulation of these EMT-promoting genes, as previously done for breast cancer (42), and the existence of a possible balance between them that controls cancer differentiation.…”
Section: Discussionmentioning
confidence: 59%
“…Wnt signaling has been implicated in EMP [52], consistent with the selective methylation of APC in epithelial cell lines. AKR1B1 has also been shown to be involved in EMT where its over-expression is associated with up-regulation of EMT markers in lens epithelial cells [53], and the selective absence of AKR1B1 methylation in mesenchymal cell lines consistent with the potential role in breast cancer EMT recently reported in basal breast cancers [54].…”
Section: Discussionsupporting
confidence: 67%
“…In this regard, higher COX2 expression and PG levels have been detected in different tumors, which could explain the NSAIDs beneficial effects in cancer prevention and treatment (3). Prostaglandin F2 (PGF2) has been scarcely studied on cancer although it has been detected in several tumor types and cancer patient body fluids (4,5) and only recently has been mechanistically associated with cancer progression (6). PGF2 is produced through the combined action of cyclooxygenases (COX) and different isomerases, AKR1B1 and AKR1C3 among others, with scarce reports implicating them in cancer (7).…”
Section: Introductionmentioning
confidence: 99%
“…Luciferase activity was quantified obtaining the ratio samples/control.Tumor growth in nude mice:In all cases, the minimum cell number indicated for each xenograft model was used. In the case of A2780 and TOV122D cell lines, 10 6 and 5x104 cells were injected subcutaneously in 6 week old female Rag2/Il2rg Double Knockout mice (R2G2, ENVIGO, France). For the SKOV3-Luc subcutaneous and intraperitoneal xenograft models, 6-week-old female Swiss Nude mice (Crl:NU (Ico)-Foxn1 nu , Charles River Laboratories) were injected with 1X10 6 cells, following the instructions of the provider of the cells, Caliper LS.…”
mentioning
confidence: 99%